2021
DOI: 10.1016/j.ijid.2020.10.061
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Japanese encephalitis in the Philippines prior to routine immunization

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Children are at greater risk of JEV infection than older people in countries where the virus is endemic, as most adults are exposed to infection during childhood. 1,22,23 However, our findings and the preliminary results of the NSW serosurvey 19 activities), or the greater lifetime risk of exposure through travel. Older seropositive participants may also have been exposed to other flaviviruses, such as MVEV, including during the large 1974 outbreak (25 of 27 JEV IgG-seropositive participants were aged 50 years or more), and our test results may have been confounded by antigenic cross-reactivity.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Children are at greater risk of JEV infection than older people in countries where the virus is endemic, as most adults are exposed to infection during childhood. 1,22,23 However, our findings and the preliminary results of the NSW serosurvey 19 activities), or the greater lifetime risk of exposure through travel. Older seropositive participants may also have been exposed to other flaviviruses, such as MVEV, including during the large 1974 outbreak (25 of 27 JEV IgG-seropositive participants were aged 50 years or more), and our test results may have been confounded by antigenic cross-reactivity.…”
Section: Discussionmentioning
confidence: 50%
“…We found that sex was not a statistically significant risk factor for infection, but in regions where JEV is endemic boys and men are more likely to be infected, experience clinical illness, and have poor outcomes than girls and women. 5,22 As 18 of 45 cases of Japanese encephalitis in Australia since 2021 were in men aged 60 years or older, 26 further investigations in immunologically naïve populations are needed.…”
Section: Discussionmentioning
confidence: 99%
“…The estimated incidence of severe JE disease in the district (approximately 1 case per 100,000) is similar to other low endemic countries before introduction of the vaccine and lower than many highly endemic regions 26,27 . On average under 1% of the population gets infected annually, and around 1:1,000 of infections result in severe disease and 1:10.000 result in death.…”
Section: Discussionmentioning
confidence: 55%
“…5 articles also grouped patient outcome into severe/moderate/minor yet based on the degree of independent functioning and controllability of seizures or the author’s subjective assessment [ 17 , 83 – 86 ]. 4 articles adopted Modified Rankin Scale to measure the degree of disability or dependence in the daily activities [ 87 90 ]. 3 articles used Glasgow Coma Scale [ 91 93 ] and the remaining 2 articles used the Whitely’s method [ 94 , 95 ].…”
Section: Resultsmentioning
confidence: 99%